Allelic frequencies of genes associated with productive traits in western Mexican boars - Ayala-Valdovinos, Miguel; Galindo-García, Jorge; Duifhuis-Rivera, Theodor; Michel-Regalado, Néstor; Virgen-Méndez, Abraham; García-Sánchez, Luís (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
The ESR1, PRLR, and RYR1 genes have previously been associated with traits of productive interest. The objective of this study was to determine the allelic frequencies of genes associated with productive traits in boars from pig farms in western Mexico. A total of 140 boars of six breeds, Duroc, Hampshire, Landrace, Piétrain, and Yorkshire, and Yorkshire/Landrace crosses were sampled. The pigs were genotyped via polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) techniques. The two alleles of the ESR1 gene were identified in the six breeds, but only BB homozygotes were recognized in Yorkshire pigs (0.2) and their crosses (0.05). The A and B alleles of the PRLR gene were distinguished in all the breeds studied, recognizing a considerable variability in the allele frequencies. Due to the allelic diversity and its effects evidenced in previous publications, it is suggested to evaluate the association of each genotype with the reproductive parameters to be improved in order to determine which genotype is more relevant in each population. In the RYR1 gene, the mutant allele causing PSS was found in all the breeds studied, which can generate pigs with PSE meat. It is recommended that the selection of boars of any breed to be used as breeders includes a genotyping test. Knowing the genotypes in boars can be used as a way to select better breeders.